2011
DOI: 10.1016/j.injury.2011.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Elevated transforming growth factor-beta 1 (TGF-β1) levels in human fracture healing

Abstract: IntroductionTransforming growth factor-beta 1(TGF-β1) is a regulatory protein, involved in bone fracture healing. Circulating TGF-β1 levels have been reported to be a predictor of delayed bone healing and non-union, suggesting active relationship between tissue and circulating TGF-β1 in fracture healing. The purpose of this study was to analyse TGF-β1 local and serum concentrations in fracture healing to further contribute to the understanding of molecular regulation of fracture healing.Patients and methodsSer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 37 publications
7
94
1
2
Order By: Relevance
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In a recent study our group demonstrated a significant increase in the TGF-β1 concentration in fracture haematoma and in serum of patients with long bone fracture. These results indicated the importance of this cytokine for fracture healing and confirmed other clinical and experimental studies [8][9][10][11][12][13][14][15][16][17]. Circulating TGF-β1 levels were found to be a predictor of delayed bone healing and non-union [11].…”
Section: Introductionsupporting
confidence: 85%
“…Patients gave informed written consent to be enrolled in the study, and were 18-90 years old. The recruitment parameters, sample collection schedule, matching process, patient demographics and exclusion criteria of this study have been previously published in detail [8][9][10]. In brief, between 2006 and 2008 a consecutive series of 113 patients with meta-/ diaphyseal fractures of long bone (humerus, femur, lower leg and forearm) and surgical treatment were included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Plasma levels of TGF-β1 for all patients (A), and for normal union group (B) showed a maximal peak at 3-week and 2-week respectively while that for nonunion group (C) showed a delayed maximal peak at 3-week as compared to normal union group. 11 . Also, TGF-β1 levels were significantly higher in fracture hematoma as compared to peripheral serum of the patients but no significant difference was found between patients with normal healing and those with delayed fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Nonunion was defined based on conventional definition as no bony healing obtained in 6 months after the fracture evidenced by specific radiological features showing bone ending changes 11 . During the course of the study, we experienced 10 patients with lower limb fracture who developed nonunion.…”
Section: Patientsmentioning
confidence: 99%